RÓŻNORODNOŚĆ TECHNIK UCZENIA SIĘ SŁOWNICTWA W JĘZYKU OBCYM - Gorąca-Sawczyk, Gabriela (Neofilolog, 2019)
In this article I will concentrate on various techniques for learning and teaching vocabulary that support the memorizing of new words, and I will present the results of a survey conducted among students of applied linguistics on this topic. The main aim of this article is to verify the hypothesis that students haven’t yet been exposed to different techniques for effective vocabulary learning. First, I will show what the mental lexicon is and how it is organised. How mnemonists learn will also be discussed. Then I will briefly explain the terms ‘vocabulary’ and ‘lexical competence’ and show the important principles of vocabulary training. At the end, I will present the most important results of my survey (opinion poll).